Neurobiological basis of emotions - Ensuncho Hoyos, Carlos (2023)
Advances in science and technology in recent years have made possible the emergence of new and powerful non-invasive neuroimaging techniques to analyze the neural networks and circuits involved in the brain. These techniques have made it possible to study the brain as never before, and have  led to numerous investigations that bring us ever closer to understanding the complex neural network that underlies the different emotional states that are part of human nature. Advances in neuroscience have allowed the construction of hypotheses that allow us to better understand and comprehend emotions, especially through studies involving important brain areas such as the limbic system. This paper presents updated information on the neurobiology of some emotional states such as fear, anger, empathy, love, sadness and depression. For this purpose, a review of the main brain areas related to these emotions is presented, while the most relevant networks and circuits that are part of and allow these emotional states are exposed.